Predictive value of heart rate in treatment of major depression with ketamine in two controlled trials. Issue 6 (June 2021) - Meyer, Torsten; Brunovsky, Martin; Horacek, Jiri; Novak, Tomas; Andrashko, Veronika; Seifritz, Erich; Olbrich, Sebastian
Highlights: Ketamine as a fast-acting agent for treating major depressive disorder. Neurophysiological markers such as electrocardiogram derived heart rate variability could be used to predict treatment outcome. This work reveals the predictive power of heart rate and heart rate variability markers for the prediction of outcome to ketamine treatment. Abstract: Objective: Ketamine has been shown to be effective in treatment of episodes of major depressive disorder (MDD). This controlled study aimed to analyse the predictive and discriminative power of heart rate (HR) and heart rate variability (HRV) for ketamine treatment in MDD. Methods: In 51 patients, HR and HRV were assessed at baseline before and during ketamine infusion and 24 hours post ketamine infusion. Montgomery–Åsberg Depression Rating Scale (MADRS) was used to assess changes of depressive symptoms. A 30% or 50% reduction of symptoms after 24 hours or within 7 days was defined as response. A linear mixed model was used for analysis. Results: Ketamine infusion increased HR and HRV power during and after infusion. Responders to ketamine showed a higher HR during the whole course of investigation, including at baseline with medium effect sizes (Cohen's d = 0.47–0.67). Furthermore, HR and HRV power discriminated between responders and non-responders, while normalized low and high frequencies did not. Conclusion: The findings show a predictive value of HR and HRV power for ketamine treatment. This further underlines the importance of the autonomous nervous system (ANS) and its possible malfunctions in MDD. Significance: The predictive power of HR and HRV markers should be studied in prospective studies. Neurophysiological markers could improve treatment for MDD via optimizing the choice of treatments.